(untitled) (Applied Biological Research, 2015)
Mastitis is a production disease with severe economic impact on the dairy industry worldwide. In the present study, weanalyzed TLR4 gene in Jersey and Holstein Frisian (HF) crossbred cattle (n = 30 each) for genetic polymorphism and its association with the severity of mastitis. Animals were selected on history of the mastitis and screening by California mastitis test (CMT) and electrical conductivity (EC). The genetic polymorphism in Toll-like receptor (TLR4) gene was analyzed by PCR-RFLP in exon1 and exon2 using HaeIII/DpnI and HinfI/TruI enzymes, respectively. The screening of milk revealed that the normal animals with CMT negative or trace have EC value in the range of 3.7- 4.9 mS cm-1, subclinical mastitis with CMT 1 or 2 in the range of 5.2-5.7 mScm-1 and clinical mastitis with CMT 3 or above in the range of 6.8-7.3 mS cm-1. The exon1 exhibits polymorphism at HaeIII site, but not at DpnI site, with three prevalent genotypes in both the breeds. The exon2 revealed polymorphism at HinfI site with three genotypes and at TruI site having two genotypes in both the breeds. A significant association was observed between mastitis and polymorphism at HaeIII site in exon1 and HinfI site in exon2 of TLR4 gene in HF cross bred cattle only. The results demonstrated that TLR4 gene may be the candidate genetic biomarker for marker assisted selection (MAS) against mastitis in crossbred dairy cattle in Kashmir.